Quality Investing: the Role of Profitability to Separate Good From Bad Stock in Value Investing (International Journal of Scientific Research and Management (IJSRM), 2021)
This paper examines how company measurement of profitability can be used to enhance the return of value investing strategy. In value investing strategy, stocks that are deemed cheap based on certain measurement are purchased. It is expected that the price of cheap stocks will increase in the future, and thus resulting in high return. In the heart of this strategy is the assumption that investors overreact to bad news. Thus bad news of a company will result in reduction of stock price below its fundamental value, resulting in undervaluation of the stock. The problem with this strategy is that not all cheap stocks are undervalued. Some cheap stocks are genuinely problematic, and their cheap valuation is already reflecting the fair value of the stocks. Thus portfolio formed using value investing might contain cheap stocks that are not undervalue, but instead fairly valued in that cheap level. One way to screen fairly valued cheap stock is by using profitability measurement as addition to value measurement. In this way stocks that are chosen are cheap stocks of the company with high profitability, and thus enhancing the probability of undervalued stocks. In this research, it is found that adding ROIC to the usual PER factor in value investing strategy increases that one year portfolio return. Quality investing, in which profitability measurement is added to value measurement in value investing, is thus a potential strategy to be used by investor